Laboratory blood lactate profile is suited to on water training monitoring in highly trained rowers - Bourdin, M.; Messonier, L.; Lacour, J. R. (The Journal of Sports Medicine and Physical Fitness, 2004)
AIM: This study validated the laboratory testing used to monitor on water training. The purpose was to test that reference heart rates (HR) determined during an incremental test elicit comparable blood lactate levels ([La](b)) during a 30 min on water rowing. METHODS: Blood lactate profile were determined during incremental graded exercise in 14 national and international level oarsmen. The HR corresponding to [La](b) of 2 and 3 mmol x l(-1) were determined (HRLa2 and HRLa3 respectively). The rowers then performed a 30 min training session in a boat. Training intensity, as assessed by HR monitors, had to range between HRLa2 and HRLa3. Field [La](b) (Laf) and HR (HRf) were measured at the end of the training session. RESULTS: Laf was 2.13+/-0.49 mmol x l(-1) (range: 1.43-3.07) and did not differ significantly from 2 mmol x l(-1). HRf (162+/-7.4 beats x min(-1)) ranged from HRLa2 (159+/-9.5 beats x min(-1)) to HRLa3 (171+/-9 beats x min(-1)). HRf was not significantly different from HRLa2. CONCLUSIONS: It was concluded that the HR determined during the laboratory testing are valid for monitoring on water training in highly trained rowers.